PERAN KIAI ABDURRAHMAN DALAM MENANGANI PASIEN ODGJ - Fakhruz Zain; Jamalul Muttaqin (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2024)
Generally, the role of a kiai encompasses not only spiritual aspects but also social ones, including social interactions and social ecology. A kiai is not only a mediator of Islamic law and doctrine but also an agent of social change and a cultural intermediary. The objective of this research is to explore the role of Kiai Abdur Rahman in handling patients with mental disorders and the factors that hinder his efforts. This research employs a qualitative approach aimed at describing and analyzing the role of the kiai in providing counseling services to students with mental disorders at the Al-Bajigur Islamic Boarding School. Located in Tenunan, Manding District, Sumenep Regency, the Al-Bajigur Islamic Boarding School serves as a place for Islamic religious education and rehabilitation, led by the kiai who provides education, guidance, and counseling to students to foster good behavior aligned with Islamic teachings and to encourage positive behavioral changes. As mentioned earlier, the role of Kiai Abdur Rahman is more complex than that of other kiais. Furthermore, the collected data and information are analyzed using relevant theories, and the conclusions are verified. The findings of this research indicate a positive impact and significant improvements compared to the previous situation.